2019
DOI: 10.1021/acsomega.9b02246
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Green Assembly-Mediated Migration of Piperine from Calf-Thymus DNA: A New Possibility of the Tunable Drug Delivery System

Abstract: Biocompatible surface-active ionic liquid (SAIL) was used first to study the deintercalation process of a well-known natural compound piperine (PIP) as an anticancer drug, obtained from PIP–calf thymus DNA (ctDNA) complex under controlled experimental conditions. In this study, we have been exploring the interaction of PIP in SAIL (1-butyl-3-methylimidazolium octyl sulfate ionic liquid ([C4mim][C8OSO3])), ctDNA, and deintercalation of PIP from the PIP–ctDNA complex through SAIL micelle using various spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…This decrease in CMC could be explained by the hydrophobic interactions between ActD and bile salts which further strengthen the hydrophobicity of studied bile salts and make their micellization process easier thereby decrease the CMC values. Differing surfactant micelles, [35][36][37][38][39] liposomes 40,41 or surface active ionic liquids 42 were studied for the effective sequestration of drugs after their deintercalation from DNA double helix. The binding of actinomycin D to DNA leads to an increase of melting temperature (Tm) of DNA with about 10 o C and this high positive value proves the intercalation binding mode of actinomycin D to DNA.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This decrease in CMC could be explained by the hydrophobic interactions between ActD and bile salts which further strengthen the hydrophobicity of studied bile salts and make their micellization process easier thereby decrease the CMC values. Differing surfactant micelles, [35][36][37][38][39] liposomes 40,41 or surface active ionic liquids 42 were studied for the effective sequestration of drugs after their deintercalation from DNA double helix. The binding of actinomycin D to DNA leads to an increase of melting temperature (Tm) of DNA with about 10 o C and this high positive value proves the intercalation binding mode of actinomycin D to DNA.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…115 Maurya et al found that the surfactant IL(SAIL) (1-butyl-3methylimidazolium octyl sulfate IL ([C 4 mim [C 8 OSO 3 ]]) can self-assemble into micelles that do not interfere with the structure of calf thymus DNA, and can relocate piperine molecules from calf thymus DNA to SAIL micelles. 116 Because the controlled release of drugs can be realized simply by changing the concentration and composition of SAIL, it provides us with a new strategy of drug deintercalation through SAIL. Gaitor et al described a novel IL based on imidazolium and ammonium, which has two C 12 and C 14 tails and a thioether linker designed for lipid complex mediated DNA delivery.…”
Section: ■ Ils For Oral Delivery Of Macromoleculesmentioning
confidence: 99%
“…Below the CMC, Triton-X 114 is unable to extract the drug molecules from DNA, but beyond its CMC, the surfactant is found to extract the DNA-intercalated safranin O. CD spectroscopy further validated that the secondary structure of DNA is not influenced by Triton-X 114 at both premicellar and micellar concentrations, thereby making the non-ionic surfactant an effective drug-sequestrating probe [32]. Different drug-sequestrating agents for various biomolecular/bio-replicating systems are tabulated in Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In this section, we will discuss the mechanism of the sequestration of Harmane (HM) bound to herring sperm DNA, using the cationic surfactant CTAB [29].…”
Section: Introductionmentioning
confidence: 99%